Relationship between plasma atherogenic index and subclinical hypothyroidism: an analysis of NHANES data and animal experiment - Chen, Qiwei; Li, Yuwan; Ruan, Yi; Jin, Linxi; Yao, Shuhong; Han, Zhuang; Hong, Xinmiao; Wang, Zhita; Li, Liang; He, Weidong; Yang, Liuqing; Heng, Xianpei (Frontiers in Endocrinology, 2025)
BackgroundThe relationship between subclinical hypothyroidism (SCH) and dyslipidemia is established, but that between the atherogenic index of plasma (AIP) and SCH remains unknown. This study aimed to investigate this association by combining an analysis of NHANES data with experimental evidence from an animal experiment.MethodsCross-sectional data from 3,135 adults were analyzed. Weighted regression and linear models assessed associations between AIP (and its quartiles) and SCH and thyroid hormones. Restricted cubic splines (RCS) tested nonlinearity. Mediation analysis was utilized to identify the mediating effects of thyroid-stimulating hormone (TSH). Subgroup analyses and interaction tests were employed to explore the association between AIP and SCH. To validate these findings, a Sprague-Dawley rat model was established with a high-fat diet and the rats were divided into a control group (CG) and a model group (MG). Blood Lipid, AIP and thyroid function (TSH, FT3, FT4) were measured in each group.ResultsAfter multivariable adjustment, the highest AIP quartile (Q4) significantly correlated with higher SCH prevalence. Elevated AIP associated with decreased free tetraiodothyronine (FT4) and increased total thyroxine (TT4), free triiodothyronine (FT3), total triiodothyronine (TT3), and TSH. RCS showed linear relationships of AIP with SCH, FT4, FT3, and TSH, but nonlinear with TT3 and TT4. Additionally, mediation analysis indicated that TSH accounted for 39.76% of the observed association between AIP and SCH. Animal experiments confirmed that compared with the CG, rats in the MG exhibited significantly higher levels of blood lipid, AIP and TSH, but lower levels of FT4 and FT3.ConclusionElevated AIP is significantly associated with a higher prevalence of SCH, and TSH is an interrelated factor in this association. Experimental evidence also shows a link between AIP elevation and thyroid homeostasis disruption, suggesting a relationship between AIP and thyroid dysfunction.